Pulpwood Characterization on Thespesia populnea for Industry at different age Gradation - Palanikumaran, B.; Parthiban, K. T.; selvan, R. Thirunirai (Indian Journal of Hill Farming, 2017)
The study was carried out at Forest College and Research Institute, Tamil Nadu, India using five different age gradations viz. two, three, four and five year old Thespesia populnea wood samples. About one metre length billets from the felled sample trees were collected from each tree for analysis of pulpwood properties. The billet was debarked, cleaned and labelled for analysis. Four age gradations of T. populnea were subjected to physical and chemical analysis in order to recommend suitable rotation age for pulp and paper production. Considering physical properties viz. bulk and basic density, all the age gradations were moderate to high in range which indicated their suitability as pulp wood. In the chemical analysis, the lignin content was significant parameter which was also moderate for all the age gradations and hence proved their suitability. The different age gradations of T. populnea differ for holocellulose which is essential factor for paper production. Considering this factor, among the four age gradations investigated, the superiority of five year old wood was evident due to maximum holocellulose content. The differences in anatomical characteristics viz., fibre length, fibre diameter, fibre wall thickness and fibre lumen width for two, three, four and five year old T. populnea wood samples respectively were investigated. Fibre length, Fibre diameter and Fibre wall thickness showed significant increment with respect to increase in age but lumen width decrease with age increases.